Two alternatives for High-Eficiency Isolated DC-DC Converts for High-voltage Aerospace. - Gules, Roger (2009)
Two alternatives for the implementation of an isolated dc-dc converter operating with high output voltage(kV) and supplied by an unregulated low input voltage a represented in this paper. The proposed to pologies are especially well adapted for the implementation of Travelling Wave Tube Amplifiers (TWTA) utilized in telecommunication satellite applications, due to low mass and volume and the high-efficiency reached by the proposed structures. A two-stage structure composed by a regulator connected in series with a ZVS/ZCS isolated dc-dc converter is the first topology proposed. The second topology studied is an isolated single-stage converter that maintains high-effìciency even under a large variation of the input voltage. The experimental results obtained from two prototypes are presented, considering an application with 150w of output power, total output voltage of 3.2kV and a variable input voltage from 26V to 44V. The efficiency for both converters operating with the nominal output power is higher than 93,4%.